Model Kebijakan Perkebunan Nilam di Pasaman Barat dengan Pendekatan Sistem Dinamis - Dina Rahmayanti; Rika Ampuh Hadiguna Hadiguna; Santosa Santosa; Novizar Nazir (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2019)
This study aims to design a model by providing several policy alternatives that are useful to assist the government in determining appropriate policies in increasing patchouli oil production from the supply aspect. The supply to be studied is patchouli plantations. The plantation is one of the important aspects affecting patchouli oil production. The choice of alternatives is based on testing alternative policies on a computerized model. Patchouli plantation models are made in line with real systems using system dynamics. From the results of the study, there are several policy alternatives that can be taken by the government, policies related to land expansion and conversion, policies related to increasing agricultural production, policies related to human resource improvement, policies related to agricultural equipment assistance and policies related to the use of superior seeds in plantations.